2016
DOI: 10.1038/srep30919
|View full text |Cite
|
Sign up to set email alerts
|

Screening differential circular RNA expression profiles reveals the regulatory role of circTCF25-miR-103a-3p/miR-107-CDK6 pathway in bladder carcinoma

Abstract: Circular RNAs (circRNAs), a kind of non-coding RNAs, have shown large capabilities in gene regulation. However, the mechanisms underlying circRNAs remain largely unknown so far. Recent studies demonstrated that circRNAs play miRNA sponge effects and regulate gene expression by microRNA response elements. Here, we screened circRNA expression profiles of bladder carcinoma using microarray assay. A total of 469 dysregulated circular transcripts are found in bladder cancer compared with normal tissues, among which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
337
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(345 citation statements)
references
References 37 publications
7
337
0
1
Order By: Relevance
“…CircHIPK2 increased SIGMAR1 expression by suppressing miR-124-2HG activity [22]. In bladder cancer, circHIPK3 affected the expression of heparanase by competitively binding to miR-558 [23]; circRNA MYLK and lncRNA H19 increase the expression of DNMT3, VEGFA, and ITGB1 by suppressing miR-29a-3P activity [24].…”
Section: Discussionmentioning
confidence: 99%
“…CircHIPK2 increased SIGMAR1 expression by suppressing miR-124-2HG activity [22]. In bladder cancer, circHIPK3 affected the expression of heparanase by competitively binding to miR-558 [23]; circRNA MYLK and lncRNA H19 increase the expression of DNMT3, VEGFA, and ITGB1 by suppressing miR-29a-3P activity [24].…”
Section: Discussionmentioning
confidence: 99%
“…These properties give circRNAs the potential of being ideal biomarkers for human diseases. Recent studies have revealed that circRNAs can be used as diagnostic or predictive biomarkers for hepatocellular carcinoma [11], pre-eclampsia [22], gastric cancer [23], and bladder cancer [24]. However, little is known about the role of circRNAs in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cir-ITCH inhibits the proliferation of ESCC by sponging miR-7, miR-17 and miR-214. To date, only two studies [30, 31] have revealed the altered expression of circRNAs in bladder cancer, indicating that circRNAs play important roles in the development and progression of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%